Bond behavior of CFRP-concrete bonding interface considering degradation of epoxy primer under wet-dry cycles. (19th July 2021) - Cui, Erjiang; Jiang, Shaofei; Wang, Juan; Zeng, Xinggui
Highlights: Not only epoxy but also bonding interface has been significantly effect by a corrosive environment. The proposed bond-slip model makes it more safety to evaluate the boding interface. Failure modes of the interface could transfer to the epoxy primer layer along with the aging duration. The immersion area of epoxy primer has a significant influence on the moisture absorption. Abstract: The excellent performance of the CFRP-concrete bonding interface is a key to ensure the reliability and effectiveness of the rehabilitation in concrete structures with external fiber reinforced polymer (FRP). Meanwhile, the epoxy primer, which bonded the FRP plate and the concrete substrate, is significantly affected by the aggressive environment. In this paper, two kinds of experiments which associated with the CFRP-concrete specimens and the epoxy primer after corroding in a wet-dry cycles environment were conducted. It shows that the immersion area of the epoxy primer has a significant influence on the properties of the moisture absorption, and that would lead to a degradation in the mechanical properties of the CFRP-concrete interface. Simultaneously, the failure modes of the CFRP-concrete interface presented a transformation from the epoxy/concrete interaction layer to the epoxy primer layer along with the increase of aging duration. To further depict the degraded bond behavior, a time-dependent bond-slip model considering the degradation of epoxy primer was proposed, and the interface fracture energy was utilized to quantify the degree of the deterioration. By comparing with the value of interface fracture energy, it was figured out that the normal bond-slip model (Popovics model) is not enough for the safety of the concrete structures rehabilitated with external CFRP, and the proposed time-dependent bond-slip model is more accurate in evaluating the time-dependent mechanical properties of concrete structures suffering in an aggressive environment.